Drug-evoked plasticity: do addictive drugs reopen a critical period of postnatal synaptic development? - Bellone, Camilla; Luscher, Christian (Frontiers in Molecular Neuroscience, 2012)
As in other parts of the central nervous system of the mouse, glutamatergic synapses onto dopamine (DA) neurons in the ventral tegmental area (VTA) mature postnatally. At birth many AMPARs lack GluA2R subunit and most NMDARs contain the GluN2B subunit. Within two weeks these receptors are replaced with GluA2- and GluN2A- containing AMPARs and NMDARs, respectively. Recent data suggest that a single injection of cocaine (or another drug of addiction) triggers glutamate receptor redistribution with the reappearance of the subunits typically present in immature synapses, as if addictive drugs reopen the developmental critical period. Here we review the experimental evidence for this hypothesis and discuss the implications for circuit function.